12 : 3 + 3 - 7 + 10 =
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,-\frac{4}{7}+\left(-\frac{2}{3}+\frac{3}{7}\right)=-\frac{4}{7}-\frac{2}{3}+\frac{3}{7}=-\frac{4}{7}+\frac{3}{7}-\frac{2}{3}=-\frac{1}{7}-\frac{2}{3}=-\frac{17}{21}\)
\(b,-\frac{3}{10}\cdot\frac{5}{12}+-\frac{3}{10}\cdot\frac{7}{12}+5\cdot\frac{3}{10}=\frac{3}{10}\cdot-\frac{5}{12}+\frac{3}{10}\cdot-\frac{7}{12}+5\cdot\frac{3}{10}=\frac{3}{10}\cdot\left(-\frac{5}{12}-\frac{7}{12}+5\right)\)
\(=\frac{3}{10}\cdot4=\frac{6}{5}\)
ti ck nha
đúng đó
xin đó
#####
\(\frac{-4}{7}+\left(\frac{-2}{3}+\frac{4}{7}\right)\)
\(=\frac{-4}{7}+\frac{-2}{3}+\frac{4}{7}\)
\(=\left(\frac{-4}{7}+\frac{4}{7}\right)+\frac{-2}{3}\)
\(=0+\frac{-2}{3}=\frac{-2}{3}\)
~ Hok tốt ~
\(\frac{-3}{10}.\frac{5}{12}+\frac{-3}{10}.\frac{7}{12}+5\frac{3}{10}\)
\(=\frac{-3}{10}.\frac{5}{12}+\frac{-3}{10}.\frac{7}{12}+\frac{53}{10}\)
\(=\frac{-3}{10}.\left(\frac{5}{12}+\frac{7}{12}\right)+\frac{53}{10}\)
\(=\frac{-3}{10}.1+\frac{53}{10}\)
\(=\frac{-3}{10}+\frac{53}{10}=\frac{50}{10}=5\)
~ Hok tốt ~
\(1)\)\(-\dfrac{10}{11}.\dfrac{8}{9}+\dfrac{7}{18}.\dfrac{10}{11}\)
\(=\dfrac{10}{11}\left(-\dfrac{8}{9}+\dfrac{7}{18}\right)\)
\(=\dfrac{10}{11}\left(\dfrac{-16}{18}+\dfrac{7}{18}\right)\)
\(=\dfrac{10}{11}.\left(-\dfrac{1}{2}\right)=-\dfrac{5}{11}\)
\(2)\)\(\dfrac{12}{25}.\dfrac{23}{7}-\dfrac{12}{7}.\dfrac{13}{25}\)
\(=\dfrac{12}{7}.\dfrac{23}{25}-\dfrac{12}{7}.\dfrac{13}{25}\)
\(=\dfrac{12}{7}.\left(\dfrac{23}{25}-\dfrac{13}{25}\right)\)
\(=\dfrac{12}{7}.\dfrac{2}{5}=\dfrac{24}{35}\)
\(3)\)\(\dfrac{3}{7}.\dfrac{16}{15}-\dfrac{2}{15}.\dfrac{-3}{7}\)
\(=\dfrac{3}{7}.\dfrac{16}{15}-\dfrac{3}{7}.\dfrac{-2}{15}\)
\(=\dfrac{3}{7}.\left(\dfrac{16}{15}+\dfrac{2}{15}\right)\)
\(=\dfrac{3}{7}.\dfrac{18}{15}=\dfrac{18}{35}\)
\(4)\)\(-\dfrac{4}{13}.\dfrac{5}{17}+\dfrac{-12}{13}.\dfrac{4}{17}\)
\(=-\dfrac{4}{13}.\dfrac{5}{17}+\dfrac{-4}{13}.\dfrac{12}{17}\)
\(=-\dfrac{4}{13}.\left(\dfrac{5}{17}+\dfrac{12}{17}\right)\)
\(=-\dfrac{4}{13}.\dfrac{17}{17}=-\dfrac{4}{13}\)
`#040911`
`1)`
`-10/11 * 8/9 + 7/18 . 10/11`
`= 10/11 * (-8/9 + 7/18)`
`= 10/11 * (-1/2)`
`= -5/11`
`2)`
`12/25 * 23/7 - 12/7 *13/25`
`= 12/7 * 23/25 - 12/7 * 13/25`
`= 12/7 * (23/25 - 13/25)`
`= 12/7 * 2/5`
`= 24/35`
`3)`
`3/7 * 16/15 - 2/15 * (-3)/7`
`= 3/7 * (16/15 + 2/15)`
`= 3/7 * 6/5`
`= 18/35`
`4)`
`-4/13 * 5/17 + (-12)/13 * 4/17`
`= -4/17 * 5/13 + (-12)/13 * 4/17`
`= 4/17 * (-5/13 - 12/13)`
`= 4/17 * (-17)/13`
`= -4/13`
`4/7 + 3/4 + 2/7 = (4/7 + 2/7 ) +3/4 = 6/7 + 3/4 = 24/28 + 21/28 =45/28`
`18/7 - 2= 18/7 - 2/1 = 18/7 - 4/7 `
`10/12 - 12/36=30/36 - 12/36=18/36=1/2`
`5/3 - 3/5 + 6/11=(25/15-9/15) + 6/11 =16/15 + 6/11 = (506+90)/165=596/165`
`3/5 xx 3/7 : 5 = 3/5 xx3/7 xx 1/5 = 9/35 xx 1/5 = 9/175`
a)\(\frac{3^{10}.\left(-5\right)^{21}}{\left(-5\right)^{20}.3^{12}}=\frac{-5}{9}\)
b)\(\frac{\left(-11\right)^5.13^7}{11^5.13^8}=-\frac{1}{13}\)
c)\(\frac{2^{10}.3^{10}-2^{10}.3^9}{2^9.3^{10}}=\frac{2^{10}.3^9\left(3-1\right)}{2^9.3^{10}}=2\)
d(\(\frac{5^{11}.7^{12}+5^{11}.7^{11}}{5^{12}.7^{12}+9.5^{11}.7^{11}}=\frac{5^{11}.7^{11}\left(7+1\right)}{5^{11}.7^{11}\left(35+9\right)}=\frac{1}{6}\)
\(C=\frac{2^{12}\left(3^5-3^4\right)}{2^{12}\left(3^6+3^7\right)}-\frac{5^{10}\left(7^3-7^4\right)}{5^{10}\left(7^3+14^3\right)}\)
\(C=\frac{3^4\left(3-1\right)}{3^6\left(1+3\right)}-\frac{7^3\left(1-7\right)}{7^3+\left(2.7\right)^3}\)
\(C=\frac{2}{9.4}-\frac{7^3.\left(-6\right)}{7^3\left(1+8\right)}\)
\(C=\frac{2}{36}-\frac{-6}{9}=\frac{13}{18}\)
\(\left(1\right)\dfrac{-7}{12}.\dfrac{11}{8}-\dfrac{37}{8}.\dfrac{7}{12}+\dfrac{1}{2}=-\dfrac{7}{12}.\left(\dfrac{11}{8}+\dfrac{37}{8}\right)+\dfrac{1}{2}=-\dfrac{7}{12}.6+\dfrac{1}{2}=-3.\)
\(\left(2\right)\left(\dfrac{2}{3}-\dfrac{1}{4}-\dfrac{5}{6}\right).\left(-2\right)^2+\dfrac{3}{2}:\dfrac{-15}{4}=\dfrac{-5}{12}.4-\dfrac{2}{5}=\dfrac{-5}{3}-\dfrac{2}{5}=\dfrac{-31}{15}.\)
\(\left(3\right)\dfrac{-2}{5}+\dfrac{3}{10}-\dfrac{3}{5}+\dfrac{7}{10}-\dfrac{3}{2}=1-1-\dfrac{3}{2}=-\dfrac{3}{2}.\)
1. \(\dfrac{-7}{12}.\dfrac{11}{8}-\dfrac{37}{8}.\dfrac{7}{12}+\dfrac{1}{2}=\dfrac{-7}{12}\left(\dfrac{11}{8}+\dfrac{37}{8}\right)+\dfrac{1}{2}=\dfrac{-7}{12}.\dfrac{6}{1}+\dfrac{1}{2}=\dfrac{-7}{2}+\dfrac{1}{2}=\dfrac{-6}{2}=-3\)2.
\(\left(\dfrac{2}{3}-\dfrac{1}{4}-\dfrac{5}{6}\right).\left(-2\right)^2+\dfrac{3}{2}:\dfrac{-15}{4}=\dfrac{-5}{12}.4+\dfrac{-2}{5}=\dfrac{-5}{3}+\dfrac{-2}{5}=\dfrac{-31}{15}\)
3.
\(\dfrac{-2}{5}+\dfrac{3}{10}-\dfrac{3}{5}+\dfrac{7}{10}-\dfrac{3}{2}=\dfrac{-4}{10}+\dfrac{3}{10}-\dfrac{6}{10}+\dfrac{7}{10}-\dfrac{15}{10}=\dfrac{-15}{10}=\dfrac{-3}{2}\)
12 : 3 + 3 - 7 + 10 = 10
Ai tích mình mình tích lại
=10 nha